2021
DOI: 10.3390/ijerph18105128
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Cadmium by Molecular Sieve and Wollastonite Is Soil pH and Organic Matter Dependent

Abstract: The excessive cadmium (Cd) concentration in agricultural products has become a major public concern in China in recent years. In this study, two amendments, 4A molecular sieve (MS) and wollastonite (WS), were evaluated for their potential passivation in reducing Cd uptake by amaranth (Amaranthus tricolor L.) in six soils with different properties. Results showed that the responses of amaranth biomass to these amendments were soil-property-dependent. The effects of MS and WS on soil available Cd were in turn de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Studies have reported that the application of 5% and 10% biochar to soil can reduce Cd, Zn, and Pb concentrations after 56 days of application (He et al, 2015). The use of manure and clay mineral amendments decrease Cd translocation from root to the wheat shoot (Hamid et al, 2019); while the addition of animal-derived organic matter can reduce Cd uptake by up to 38% in spinach crop (Sato et al, 2010); furthermore in amaranth shoots, it is possible to inhibit cadmium accumulation with the use of a combination of organic amendments (Dong et al, 2021). Hence the interest in finding the most viable strategies for agricultural producers, since heavy metals in soil can cause in addition to plant stress, alterations in growth and a reduction in crop yield (Nagajyoti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that the application of 5% and 10% biochar to soil can reduce Cd, Zn, and Pb concentrations after 56 days of application (He et al, 2015). The use of manure and clay mineral amendments decrease Cd translocation from root to the wheat shoot (Hamid et al, 2019); while the addition of animal-derived organic matter can reduce Cd uptake by up to 38% in spinach crop (Sato et al, 2010); furthermore in amaranth shoots, it is possible to inhibit cadmium accumulation with the use of a combination of organic amendments (Dong et al, 2021). Hence the interest in finding the most viable strategies for agricultural producers, since heavy metals in soil can cause in addition to plant stress, alterations in growth and a reduction in crop yield (Nagajyoti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%